Anterior Slope Correction-Flexion Osteotomy in Traumatic Genu Recurvatum - Ramos Marques, N (2022)
A decreased posterior tibial slope has been associated with an increased risk of posterior cruciate ligament failure, anterior knee pain, and premature knee osteoarthritis. Trauma is a common cause of osseous genu recurvatum. Surgical management is recommended to correct the tibial slope and prevent knee pain and osteoarthritis progression. This article discusses our preferred treatment using a proximal tibial opening-wedge osteotomy for surgical management of genu recurvatum secondary to significant anterior tibial slope.